Biomass juncus derived carbon modified with Fe3O4 nanoparticles toward activating peroxymonosulfate for efficient degradation of tetracycline. (February 2023) - Zhang, Yujie; Yang, Qin; Yue, Luchao; Liu, Qian; Luo, Yongsong; Wu, Junyou; Kang, Xiaowen; Sun, Shengjun; Yang, Yingchun; Sun, Xuping
Abstract: In this work, Fe3 O4 nanoparticles anchored biomass juncus derived carbon (Fe3 O4 @JDC) was developed as a highly efficient heterogeneous peroxymonosulfate (PMS) activator to degrade organic pollutants. As-prepared catalyst was characterized by X-ray diffraction, scanning electron microscopy, transmission electron microscopy, X-ray photoelectron spectroscopy, and vibrating sample magnetometer techniques. High loading and good dispersion of Fe3 O4 nanoparticles on JDC lead to excellent degradation performance for tetracycline (90.2 %, 60 min) and other pollutants (above 80 %), and the reaction rate constant (k) is 3.73 times (0.0384 min −1 ) than that of pure JDC (0.0103 min −1 ) in the presence of PMS. Additionally, chemical oxygen demand (COD) removal rate of Fe3 O4 @JDC/PMS system (64.7 %, 60 min) is best than other systems (JDC system, JDC/PMS system, etc.). The quenching tests and electron paramagnetic resonance (EPR) data further demonstrate that TC degradation is an integrative contribution of both non-radical ( 1 O2 ) and free radical (O2 −, SO4 −, and OH) pathways. Furthermore, Fe3 O4 @JDC also exhibits superior reusability (81.1 % degradation efficiency after five cycles) and magnetic separation ability. Graphical abstract: High loading and good dispersion of Fe3 O4 nanoparticles significantly improves the peroxymonosulfate activation performance of juncus derived carbon (JDC) to generate active species for catalytic degradation of tetracycline (90.2 %) and other pollutants (above 80 %) rapidly. Unlabelled Image Highlights: Fe3 O4 nanoparticles anchored juncus derived carbon (Fe3 O4 @JDC) was synthesized via soaking coupled with calcination. It was applied as a peroxymonosulfate activator to generate active species for degrading pollutants. Magnetic Fe3 O4 @JDC showed superior catalytic performance and provides a simple separation way.